Saponin Interactions with Model Membrane Systems – Langmuir Monolayer Studies, Hemolysis and Formation of ISCOMs - de Groot, Carolin; Müller-Goymann, Christel C. (Planta Medica, 2016)
Saponins are used in medicine due to their pharmacological and immunological effects. To better understand interactions of saponins with model membranes and natural membranes of, for example, erythrocytes, Langmuir film balance experiments are well established. For most saponins, a strong interaction with cholesterol was demonstrated in dependence of both the aglycone part and the sugar moieties and is suggested to be correlated with a strong hemolytic activity, high toxicity, and high surface activity, as was demonstrated for the steroid saponin digitonin. In general, changes in the sugar chain or in substituents of the aglycone result in a modification of the saponin properties. A promising saponin with regard to fairly low hemolytic activity and high adjuvant effect is α-tomatine, which still shows a high affinity for cholesterol. An interaction with cholesterol and lipids has also been proven for the Quillaja saponin from the bark of Quillaja saponaria Molina. This triterpene saponin was approved in marketed vaccines as an adjuvant due to the formation of immunostimulating complexes. Immunostimulating complexes consist of a Quillaja saponin, cholesterol, phospholipids, and a corresponding antigen. Recently, another saponin from Quillaja brasiliensis was successfully tested in immunostimulating complexes, too. Based on the results of interaction studies, the formation of drug delivery systems such as immunostimulating complexes or similar self-assembled colloids is postulated for a variety of saponins.
Keywords: saponins; isoprenoids; hemolytic activity; ISCOM; Langmuir film balance